Apprendre le latin dans l’Égypte de l’Antiquité tardive : le rôle de la littérature latine - Scappaticcio, Maria Chiara (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2024)
Abstract Learning Latin in Late Antique Egypt: What Role Did Latin Literature Play? This paper offers an overview on how the Western educational model reached the Late Antique Eastern empire, and specifically Egypt, contributing to shape a renewed cultural identity where the literature from Rome had to find its place. With the benefit of an updated census and edition of a Corpus of Latin Texts on Papyrus (CLTP) (forthcoming with CUP), we’ll seek to explore both the technical literature and paraliterature of a grammatical and educational kind, as well as proper literary works by the scholastic canonic authors of the quadriga Messii (Terence and Virgil, Sallust and Cicero) but also works by authors who reputedly enjoyed a renewed appreciation in Late Antiquity (e.g. Livy, Juvenal). Our main focus here is the role Latin literature played in teaching/learning Latin as a foreign language in such a multilingual and multicultural context as Late Antique Egypt.